Implementation of the Rooftop Solar Power Plant (PLTS Atap) Policy Based on the Regulation of the Minister of Energy and Mineral Resources (ESDM) - Susetyaldi Rahardjo; Ade Setiadi; Susi Sugiyarsih (Gema Wiralodra, 2025)
This study examines the implementation of the Rooftop Solar Power Plant (PLTS Atap) policy as regulated under the Minister of Energy and Mineral Resources (ESDM) Regulation Number 26 of 2021 and its amendment, Regulation Number 2 of 2024, with a focus on the industrial sector, particularly PT Uni-Charm Indonesia Tbk. The purpose of this study is to analyze how the PLTS Atap policy has been interpreted and executed by private industries, the challenges encountered in its implementation, and its contribution to improving corporate environmental performance. The study also seeks to explore how corporate actors respond to state-led energy transition initiatives and adapt their business strategies to comply with renewable energy regulations. Using a qualitative descriptive approach, this research relies on primary and secondary data collected through interviews, field observations, and document studies. The research applies the policy implementation model by Van Meter and Van Horn as its analytical framework, combined with the principles of Good Environmental Governance (GEG) and the concept of sustainable energy transition. This combination allows for a comprehensive understanding of the institutional, technical, and behavioral factors influencing the adoption of rooftop solar power systems in industrial settings. The findings indicate that the implementation of PLTS Atap policy at PT Uni-Charm Indonesia Tbk has generally been successful, supported by managerial commitment, adequate resources, and cooperation between government agencies and private actors. The company’s adoption of rooftop solar power has resulted in tangible improvements in energy efficiency, cost reduction, and carbon emission mitigation, contributing to national and global climate action goals. However, the implementation process has also faced obstacles, including regulatory changes, administrative complexity, and the absence of consistent financial incentives. Despite these challenges, the PLTS Atap initiative represents a progressive step toward realizing Indonesia’s clean energy transition and enhancing private sector involvement in environmental governance.